Estudos de primeiros princípios do grafeno interagindo com clusters de dióxido de titânio - Júnior, José Solon da Silva (2018)
Recent studies demonstrate the effectiveness of nanostructures in dentistry. Some applications reduce physiological implications, such as the non-acceptance of a dental implant by the body. A promising nanostructure in several areas of knowledge that has been little explored for this purpose is graphene. In this work, we studied the interaction of adsorbed graphene with phosphorus (P), silver (Ag) and calcium (Ca) atoms with titanium dioxide clusters (TiO2), with nomenclature (TiO2)n, with n varying from 1 to 3. The aim of this study is to identify systems that are relevant to the area of implantology, i. e., nanosystems that could facilitate the adhesion of the implant to the organism. The dopant atoms were chosen because of their biocompatibility with bone tissue (P and Ca) and antibacterial properties (Ag). The clusters of TiO2 were used to mimic the oxide that is usually formed on titanium implants. For this, we performed calculations of first principles, based on the Density Functional Theory, as implemented in the SIESTA code. The exchange and correlation potential was treated within the generalized gradient approximation and the description of the valence electrons was done using the pseudopotential method. The results showed that the interaction of graphene adsorbed with calcium with TiO2 clusters is the most promising system that meets the purposes of the work. The adsorption energies for this case vary from 2.41 eV to 4.70 eV, indicating a strong interaction. In the case of silver-adsorbed graphene, the adsorption energies are lower, but still characterize a strong interaction, which varies from 1.31 eV for the cluster with n = 2 and 2.05 eV for the cluster with n = 3. For the cluster with n = 1, the value found for the adsorption energy was 1.92 eV. The system that was not relevant to the objectives of this work was the graphene adsorbed with phosphorus interacting with the clusters. In this case, the adsorption energies were high, 3.42 eV for (TiO2)1, and 2.16 eV for (TiO2)3, however, we observed that the cluster removed the atoms adsorbed from the graphene. For the cluster (TiO2)2, the interaction was weak, with an adsorption energy of 0.46 eV. These results, while theoretical, show that graphene can be a potential candidate for the creation of thin films to be used in the coating of titanium implants.